Integrasi Sains dan Al-Qur’an dalam Pembelajaran IPAS Perspektif Epistemologi Ahmad Al-Jabiri (Bayani, Burhani, dan Irfani) - Dini, Nurul Aulia; Siregar, Nasyariah; Wiratama, Arif (LP2M STIT Palapa Nusantara, 2026)
Natural and Social Science Education (IPAS) at Madrasah Ibtidaiyah remains predominantly focused on cognitive and scientific aspects, while the integration of Islamic values, particularly verses of the Al-Qur’an has not yet been implemented in a deep and contextual manner. This study aimed to develop IPAS teaching materials that integrate science and the Al-Qur’an based on Ahmad Al-Jabiri’s epistemology, which encompasses the bayani, burhani, and irfani phases. The research employed a Research and Development (R&D) method with teachers and fifth-grade students of Madrasah Ibtidaiyah as the subjects. Data were collected through teacher and student response questionnaires, interviews, documentation, and needs analysis, and were then analyzed using both qualitative and quantitative descriptive techniques. The findings show that the developed IPAS teaching materials successfully integrate scientific concepts with Al-Qur’anic verses in a systematic and meaningful way that aligns with the characteristics of elementary-level learners. The Ahmad Al-Jabiri–based IPAS teaching materials were declared suitable for use as an integrative learning alternative that brings together rationality, empirical experience, and revelatory values in basic education. Teacher and student responses were positive, indicating that the materials are easy to understand, engaging, and helpful in enabling students to master scientific concepts while simultaneously enhancing their spiritual understanding.